Effectiveness of Using Building Spaces Media to Improve Mathematical Problem-Solving: Literature Review - Purnomo, Hadi; Siswono, Tatag Yuli Eko; Wiryanto, Wiryanto (International Journal of Emerging Research and Review, 2024)
Objectives: This study investigated the effectiveness of various spatial learning media in improving students' mathematical problem-solving. Method:   The research method used is a literature review of articles and journals on Google Scholar from 2019-2024 that discuss the media of building space. The 33 national and international journal literature reviews identified 23 digital and 10 physical media suitable for teaching the material. Results: The outcome of this study was the effectiveness of media use for spatial learning in mathematics, which showed a preference for digital media due to its engaging, dynamic, and flexible nature. In addition, the study showed that incorporating learning media into teaching spatial building can improve students' mathematical problem-solving ability, creativity, and overall interest in learning. These findings emphasize the importance of tailoring media selection to individual learning styles for optimal effectiveness. Ultimately, this study underscores the transformative potential of mathematics learning media in improving student engagement and academic achievement. Novelty: This study offers valuable insights into the benefits of media-integrated instruction for spatial building materials and its positive impact on students' problem-solving skills. As educational technology continues to evolve, this study serves as a reminder of the profound influence effective math learning media can have on a student's educational journey.